PEMISAHAN KEKAYAAN PERSEROAN TERBATAS DARI KEKAYAAN PEMEGANG SAHAM, DEWAN KOMISARIS DAN DEWAN DIREKSI - Hasnati Hasnati; Sandra Dewi; Andrew Shandy Utama (Ensiklopedia Social Review, 2019)
In order for legal entities to interact in legal relationships such as making agreements, conducting certain business activities requires capital. The initial capital of the legal entity came from the founder's wealth which was separated. The initial capital becomes the wealth of the legal entity, regardless of the founder's wealth. This article looks at how the separation of limited company wealth from the wealth of shareholders, board of commissioners and board of directors. The research methodology used is the normative juridical research method. Company Organs are the General Meeting of Shareholders, Directors and Board of Commissioners (Article 1 number 2 of the Company Law). The Board of Directors is the Company's Organ which has the authority and is fully responsible for the management of the Company for the interests of the Company, in accordance with the aims and objectives of the Company and represents the Company, both inside and outside the court in accordance with the provisions of the articles of association (Article 1 number 5 of the Company Law). Whereas the Commissioners are the Company's Organs whose duty is to supervise general and / or specifically in accordance with the articles of association and provide advice to the Directors (Article 1 number 6 of Company Law). In PT, the shareholders delegate their authority to the directors to run and develop the company in accordance with the objectives and business fields of the company. In connection with this task, directors are authorized to represent the Company, enter into agreements and contracts, and so on. If there is a very large loss (above 50%) then the board of directors must report it to the shareholders and third parties, and then close it together. Keywords: Separation of Wealth, Limited Liability Company, Shareholders' Wealth.